But-prefacing for Refocusing in Public Questioning and Answering - Ann Tai Choe; Elizabeth Reddington (Studies in Applied Linguistics & TESOL, 2019)
In this paper, we focus on a special use of but in interactions in which those doing the questioning and answering are accountable for producing talk that is relevant to a third party—an overhearing audience. Specifically, we aim to show how participants leverage the contrastive power of but in turn-initial position to refocus following a deviation from the main course of action.